Azoloazines as A2a receptor antagonists. Structure – activity relationship. (July 2018) - Savateev, Konstantin V.; Ulomsky, Evgeny N.; Butorin, Ilya I.; Charushin, Valery N.; Rusinov, Vladimir L.; Chupakhin, Oleg N.
Abstract : Non-xanthine inhibitors of the adenosine A2a receptor of the azoloazine series are good candidates for use as drugs for the treatment of neurodegenerative diseases and sepsis. This review systematizes and summarizes the structure – activity relationships in the series of triazoloazines, including annulated pyrimidines, pyrazines and triazines, as well as their tricyclic fused analogues. The above relationships for such systems are analyzed. The structures of the most efficient functional moieties from the point of view of affinity for the A2a receptor and selectivity for other types of adenosine receptors (A1, A2b, A3 ) are presented. The bibliography includes 71 references.